Comparison of Decisions under Unknown Experiments - Caplin, Andrew; Martin, Daniel (Journal of Political Economy, 2021)
We take the perspective of an econometrician who wants to determine which of two experiments provides higher expected utility but only knows the decisions under each experiment. To compare these decisions, the econometrician must make inferences about what the experiment might have been for each set of decisions. We provide a necessary and sufficient condition that identifies when every experiment consistent with one set of decisions has a higher value of information than every experiment consistent with the other set of decisions.